Case Report: Genetic Analysis of a Small Supernumerary Marker Chromosome in a Unique Case of Mosaic Turner Syndrome - Li, Chao; Luo, Weiyao; Xiao, Tingting; Yang, Xingkun; Ou, Miaoling; Zhang, Linghua; Huang, Xiang; Zhu, Xiaodan (Frontiers in Pediatrics, 2022)
Background The aim of this study was to explore the source and morphology of a small supernumerary marker chromosome (sSMC) from karyotype analysis of a patient with a unique case of mosaic Turner syndrome. The study findings will provide technical reference and genetic counseling for similar cases. Case Presentation A female patient with 46,X,+mar karyotype was diagnosed by genetic karyotype analysis. Genetic methods including fluorescence in situ hybridization (FISH) and copy number variation sequencing (CNV-seq) based on low-depth whole-genome sequencing were used to explore the source and morphology of sSMC. FISH technology showed that 56.5% of the cells were X and 43.5% of the cells were XY. CNV-seq detection found that the sSMC was chrY, implying that the patient's karyotype was mos 45,X[58.6%]/46,XY[41.4%]. Retrospective karyotype analysis indicated that the female patient's sSMC was inherited from her father's small chrY. Customized FISH probe of Yq12 microdeletion was positive, indicating that the sSMC was a del(Y)(q12). Based on the results of genetic diagnosis, the specialist doctor gave a comprehensive genetic consultation and ordered regular follow-up examinations. Conclusions The findings of the current study showed that the chromosome description of the unique Turner case was mos 45,X[56.5%]/46,X,del(Y)(q12)[43.5%]. FISH technology played a key role in diagnosis of mosaicism. The terminal deletion of mosaic chrY provided a scientific and an accurate explanation for masculinity failure and abnormal sexual development of the current case.